Investigation of the mechanic, thermal, and electrochemical corrosion behavior of Fe effect on IN718 produced by PM used in the aviation industry - Ilgazi, Muhammed Enes; Balci, Esra; Basit, Sercan; Dagdelen, Fethi; Mutlu, Ilven (Springer, 2025)
This study examined the microstructure, thermal oxidation behavior, electrical conductivity, microhardness, and corrosion behavior of Ni-Cr-Mo-Nb-Fe superalloys, depending on the Ni and Fe ratio change. When the high-temperature oxidation behaviors of the alloys were examined, it was seen that the activation energy (Eo) required for oxidation raised as the Ni ratio increased. The activation energy values were compared, and it was determined that the highest sample was PM10, 133 kJ mol-1. The oxide layers formed by the alloy elements are clearly visible in the images obtained as a result of SEM analysis. EDX peaks and results show the composition of the alloy and the presence of metal oxide compounds. It was found that the microhardness value increased when the mass ratio of Fe element was reduced and the mass ratio of Ni element reached the highest value (PM10). With the increase in addition rates of nickel, the electrical conductivity of super alloys raised. According to the CR results of the samples, PM10 exhibited a relatively high passive current density indicating a faster dissolution rate and its corrosion resistance was calculated to be significantly lower than the other samples. The analysis determined that the sample with the highest corrosion resistance was PM8. As a result, it is noteworthy that it can be used in the aviation and space industry, especially at high temperatures, due to its good resistance to corrosion.
Keywords: Oxidation; Corrosion; Superalloy; Aircraft material; Microstructure